PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL STUDI PADA KABUPATEN/KOTA DI SULAWESI TENGAH - Warasati, Ni Nyoman; Palampanga, Anhulaila M.; Iqbal B., Mohammad (Katalogis, 2018)
The purpose of this sampling study is to determine and analyze the growth of local revenue, general allocation funds and capital expenditure. Also, it intends to determine and analyze simultaneous and partial influences of local revenue and general allocation funds on capital expenditure. Sample of this study consists of 11 regencies/cities in Central Sulawesi that have been selected by purposive sampling technique. Data analysis methods are growth ratio and multiple regression analysis. The results show that the average growth of local revenue, general allocation funds and capital expenditure tend to fluctuate during 3 years of budget period. Simultaneous test indicates that local revenue and general allocation funds have positive and significant influence on capital expenditure. Partial tests prove that local revenue has insignificant influence on capital expenditure while general allocation funds has positive and significant influence on capital expenditure. Determinant coefficient R-square of 0,413 indicates that 41,30% of capital expenditure is influenced by local revenue and general allocation funds, while the remaining of 58,70% influenced by other variables that have not studied.